P294 On the way to disease control: Fatigue as part of a novel composite endpoint in an analysis of a prospective open label observation trial. (21st January 2022) - Tran, F; Nikolaus, S; Schrinner, F; Kümpers, J; Lessing, A; Lintner, J; Lessing, M; Sievers, L K; Rosenstiel, P; Aden, K; Franke, A; Schreiber, S
Abstract: Background: Ambitious therapeutic goals in the therapy of inflammatory bowel disease need more stringent individual endpoints. Several definitions for composite endpoints are under evaluation to describe disease control. Most commonly symptomatic (PRO2) remission is combined with endoscopic response, histology and/or biomarker remission. Here we explore the addition of fatigues as a lead problem reported by patients with IBD as part of a composite endpoint. Methods: We have conducted an interim analysis of an ongoing open label study of patients with Crohn's disease (CD) and ulcerative colitis (UC) assigned to anti-TNF therapy, vedolizumab, ustekinumab or tofacitinib. Patients are scheduled for evaluations at start of the respective therapy and at weeks 2, 6, 14, 26 and 52. Endoscopies are conducted before therapy and at weeks 14 and 52. Clinical remission (CR) was defined as CDAI < 150 and reduction of partial Mayo score (pMayo) > 50% vs. baseline at week 14. All patients who are not in CR and/or no improvement in endoscopy at week 14 are assessed for a switch in the mechanism of action and observation schedules after a switch are reset to week 0. FACIT-F scores <30 was defined as clinically relevant fatigue. Results: Fatigue was present in 52% patients (39/75) at baseline. 54% (25/46) of the patients achieved CR at week 14 while 46% (21/46) did not meet CR criteria (non-responder). Fatigue at baseline was persistent at week 14 in 12% (3/25) of CR responders, in contrast to 43 % (9/21) of non-responders. 64% (21/33) of all patients reached a combined endpoint of CR and absence of fatigue. If fatigue was present at baseline ( n = 25), fatigue response was observed in 52% (13/25) of the patients, while CR was only reached in 40% (10/25) and the combined endpoint of CR and fatigue response in 24% (6/25) of the patients at week 14. In contrast, 71% (15/21) of patients without fatigue at baseline reached CR at week 14. Absence of fatigue at baseline thus increased the chance of CR at week 14, with an OR of 3.75 [1.031 – 11.50] ( p = 0.0422 in Fisher's exact test). Conclusion: Fatigue is an important complaint strongly impacting the patients' quality of life. A composite endpoint including fatigue and clinical remission (based on pMayo and CDAI) can be reached in a significant percentage of patients treated with biological therapies. Presence of fatigue at baseline might serve as a strong marker for clinical non-response at week 14. Further evaluation and replication of this novel composite endpoint will be conducted in our ongoing trial with a particular focus on inclusion of endoscopies and long-term outcome.